The vampire's vacation - Roy, Ron, 1940-; Gurney, John (New York : Random House, 2004)
Dink, Josh, and Ruth Rose investigate a mysterious man in black who Josh believes is a vampire.
"A Stepping Stone Book."
2.5.
006-009.
Keywords: Vampires -- Juvenile fiction; Vampires -- Fiction; Mystery and detective stories